Review of rabies in Nepal - Pantha, Saurav (One Health, 2020)
Rabies is a global problem, but the burden is higher in less developed or developing countries of Asia and Africa. In Nepal, rabies is reported to kill around 500 animals and up to 32 human beings in recent years, with possible under-reporting of cases and deaths. As a prophylactic measure, around 30,000 livestock and 300,000 humans get vaccinated each year in Nepal. This review summarizes the past, present and future perspectives of rabies control and prevention in Nepal. The global strategic plan of World Health Organization (WHO) aims to bring human deaths from dog-transmitted rabies to zero by 2030. To achieve this goal of ‘Zero by 30’, the concerned governmental and non-governmental agencies in Nepal should work together using the One Health concept.